Pola Komunikasi Pengguna Media Sosial dalam Perilaku People Pleasing terhadap Ekspektasi Sosial - Anggraeni, Apriyani; Loisa, Riris; Irena, Lydia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2026)
The development of technology and social media encourages users to adjust their communication patterns to gain social acceptance, which in turn gives rise to the phenomenon of people pleasing in the digital space. This study examines the communication patterns of Instagram users in meeting social expectations, particularly through the phenomenon of people-pleasing, from the perspective of Erving Goffman's dramaturgy. Social media, especially Instagram, is used by users to project a more perfect self-image as part of impression management, while their true identities are more often displayed in private spaces. This study uses a qualitative approach with a phenomenological method through in-depth interviews, observation of informants' Instagram accounts, and documentation. The results show that pressure from the social environment influences how a person communicates, selects content, edits posts, and chooses language to gain recognition from others. The phenomenon of people-pleasing emerges as a way to maintain a positive image and elicit responses from the audience through various channels such as stories, comments, and direct messages. The research findings also indicate that users utilize the DM feature as a place for more authentic interactions, while public posts become a